Serum Cystatin C is Associated with Depression After Intracerebral Hemorrhage - Zhu L; Yu C; Chang Y; Sun S; Sun Z (Neuropsychiatric Disease and Treatment, 2023)
Lei Zhu,1,2 Chuanqing Yu,2 Yueyue Chang,2 Shiyu Sun,2 Zhongwu Sun1 1Department of Neurology, First Affiliated Hospital of Anhui Medical University, Hefei, Anhui Province, People’s Republic of China; 2Department of Neurology, First Affiliated Hospital of Anhui University of Science and Technology, First People’s Hospital of Huainan, Huainan, Anhui Province, People’s Republic of ChinaCorrespondence: Zhongwu Sun, Department of Neurology, First Affiliated Hospital of Anhui Medical University, Hefei, Anhui Province, People’s Republic of China, Email sunzhwu@126.comPurpose: Cystatins are associated with neuronal degeneration and nervous system healing. Cystatin C (Cys C) has recently been linked to brain injury and immunological inflammation. This study aimed to determine the relationship between serum Cys C levels and depression following intracranial hemorrhage (ICH).Patients and Methods: Between September 2020 and December 2022, 337 patients with ICH were sequentially recruited and followed up for three months. The post-stroke depression (PSD) and non-PSD groups were separated based on the 17-item Hamilton Depression Rating Scale (HAMD). The PSD diagnosis was established based on the DSM-IV criteria. Cys-C levels were documented within twenty-four hours of admission.Results: Three months after ICH, 93 (27.6%) of 337 enrolled patients were diagnosed with depression. The Cys C levels were significantly higher in depressed patients than in nondepressed patients after ICH (1.32 vs 1.01; p< 0.001). After adjusting for potential confounding variables, depression after ICH was associated with the highest quartile of Cys C levels (odds ratio (OR) = 3.195, 95% CI: 1.562– 6.536; p=0.001). The receiver operating characteristic curve (ROC) curve predicted that the ideal cut-off for CysC levels as a predictor of depression after ICH would be 0.730, resulting in 84.5% sensitivity and 88.4% specificity, with an area under curve (AUC) of 0.880 (95% CI: 0.843– 0.917; p< 0.0001).Conclusion: Increased CysC concentrations were independently related to depression three months after ICH, highlighting that CysC levels at admission may be a potential biomarker for predicting the onset of depression following ICH.Keywords: cystatin C, depression, intracerebral hemorrhage, post-stroke depression